The Influence of Brand Awereness on Purchase Decisions Moderated by Product Quality and Customer Experience as Mediation - Parhan, Parhan; Rizkillah, Renna; Salbiyana, Salma (Lentera Ilmu Nusantara, 2024)
Indonesia is the fourth largest coffee producer and exporter in the world. coffee began to enter indonesia precisely on the island of java in 1969 during the colonization by the dutch. with the promise of a coffee business in indonesia, many well-known coffee shops have emerged in indonesia today, one of which is kopi kenangan. kopi kenangan is one of the fastest-growing coffee shops or brands in indonesia. founded in 2017, kopi kenangan currently has more than six hundred stores located in several cities. this study aims to analyze more deeply the influence of brand awareness on purchase decisions moderated by product quality and customer experience as mediation of kopi kenangan products. the research method used is based on quantitative research using primary data in the form of distributing questionnaires to all students of universitas pelita bangsa. the sample used in this study was 100 respondents. . the data processing was carried out using smart-pls3 using a partial least square approach. the results showed that brand awareness had an effect on purchase decisions, it was concluded that brand awareness had a significant positive effect on product quality, product quality had a significant positive effect on purchase decisions, brand awareness had a significant positive effect on purchase decisions but insignificantly or in other words customer experience did not play a role.